Association of raloxifene and tamoxifen therapy with cognitive performance, odds of mild cognitive impairment, and brain MRI markers of neurodegeneration - Firat Kara; Christine M. Lohse; Anna M. Castillo; Nirubol Tosakulwong; Timothy G. Lesnick; Clifford R. Jack Jr; Ronald C. Petersen; Janet E. Olson; Fergus J. Couch; Kathryn J. Ruddy; Kejal Kantarci; Michelle M. Mielke (Cancer Medicine)
Abstract The aim of this cross‐sectional study was to examine whether a history of selective estrogen receptor modifiers (SERMs), tamoxifen and raloxifene, use was associated with cognitive performance, odds of mild cognitive impairment (MCI), or magnetic resonance imaging (MRI) markers of neurodegeneration associated with Alzheimer's disease. We included women with prior history of breast cancer or no prior history of any cancer at enrollment in the Mayo Clinic Study of Aging (MCSA). This information was abstracted using the Rochester Epidemiology Project medical‐linkage system. Logistic regression was used to examine associations of SERMs with odds of MCI. Linear regression models were used to examine associations of SERMs with cognitive z‐scores (Memory, Executive Function, Language, Visuospatial Skills, Global Cognition), and MRI markers. Among 2840 women aged 50 and older in the MCSA, 151 had a history of breast cancer, and 42 (28%) of these had a history of tamoxifen treatment. A total of 2235 women had no prior history of any cancer, and 76 (3%) of these had a history of raloxifene use. No significant associations between tamoxifen use and cognition, or odds of MCI were observed among women with a history of breast cancer after adjusting for confounders. Similarly, raloxifene use was not significantly associated with cognition, or odds of MCI in women without a history of cancer after adjusting for confounders. We did not find significant associations between the use of either SERM and MRI markers. Use of tamoxifen or raloxifene was not significantly associated with cognition in postmenopausal women.